Analysis of momentum strategy for generating abnormal return in the Indonesian Stock Exchange - Ida Bagus Teguh Cipta Maya Negara; Buddi Wibowo (President University, 2022)
The testing of momentum strategies by previous research on the capital markets of developed and developing countries led to different results. This study aimed to explain the momentum Strategy for generating abnormal returns in the Indonesia Stock Exchange using several factors. The factors are market factor, size, book-to-market ratio, and momentum. This study implemented formation-holding 12-3 months, 12-6 months, 12-9 months and 12-12 months. This study using Capital Asset Pricing Model, Fama French Three Factor Model, and Carhart Four Factor Model to see the effect of these factors on the excess return. The result based observation from January 2009 until December 2019 showed that momentum Strategy is unable to generating abnormal return in the Indonesia Stock Exchange. However, this research shows that the winner's portfolio by using 12-3 Strategy is able to provide a significant abnormal return of 1.02% when tested using the Capital Asset Pricing Model. Furthermore, all four of these factors (market factor, size, book-to-market ratio, and momentum) have influence in generating abnormal return on winner portfolio of the momentum Strategy.